Pengaruh kebiasaan merokok terhadap kejadian disfungsi ereksi pada petugas keamanan di Universitas Udayana Sudirman - Tifania Melucha Miguel Leong; I Made Oka Negara; Yukhi Kurniawan (DiscoverSys Inc., 2019)
Introduction: Smoking habits are behaviors that are now still seen in various country and these behaviors are really difficult to eliminate. Each cigarette dangerous chemicals like nicotine that can be effect to health especially smokers, one of this effect is erectile dysfunction. In this Study, the aim was to determine how much influence smoking habits can affect to erectile problem in security officers at Udayana University Sudirman.Methods: This is a cross-sectional descriptive study that was conducted at Udayana Universitas Sudirman with 10 participants and obtained from filling IIEF-5 questionnaire (International Index of Erectile Dysfunction) and active smoker questionnaire that were distributed directly to the participants.Result: The results of this study was shown that almost 40% security officers had mild erectile dysfunction. This study is observer from Non-Probability Sampling especially in convenient sampling to look the effect of smoking habits that against erectile dysfunction.Conclusion: The security officer at Udayana University in Sudirman with smoking habits almost all experienced erectile dysfunction with different categories of erectile dysfunction.Latar Belakang: Kebiasaan merokok merupakan perilaku yang sekarang masih terlihat di berbagai negara dan perilaku tersebut sulit untuk menghilangkannya. Pada setiap batang rokok terkandung zat kimia yang berbahaya kesehatan para perokok dan salah satunya adalah Disfungsi Ereksi. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh kebiasaan merokok terhadap kejadian DE pada petugas keamanan di Universitas Udayana Sudirman.Metode: Jenis penelitian ini adalah Cross-sectional Descriptive Study. Penelitian ini dilakukan di Kampus Universitas Udayana Sudirman dengan jumlah responden 10 orang dan didapatkan dari pengisian kuesioner IIEF-5 (International Inde of Erectile Function) dan kuesioner perokok aktif yang dibagikan secara langsung pada responden.Hasil: Dari hasil penelitian ini, menunjukan bahwa dari 10 petugas keamanan didapatkan 40% mengalami DE ringan. Di uji dari Non-Probability Sampling khususnya Convenient Sampling terhadap pengaruh kebiasaan merokok pada disfungsi ereksi.Simpulan: Petugas keamanan di Universitas Udayana Sudirman dengan kebiasaan merokok hampir seluruhnya mengalami disfungsi ereksi dengan kategori yang berbeda terhadap kejadian disfungsi ereksinya.